Re-learning Design: Pedagogical Experiments with STS in Design Studio Courses - Ignacio Farías; Tomás Sánchez Criado (Diseña, 2018)
In the last decades, design disciplines have been encountering the social sciences and humanities in inventive modes. These new collaborations entail partial redefinitions of the disciplines involved therein. On the one hand, contemporary strands of social and cultural theory – especially in the field of science and technology studies (STS), but also in anthropology – have made design much more than a mere research object. On the other hand, design disciplines have incorporated not only social research methods and ethnography, but also the type of conceptual work characteristic of social and cultural theory. This has led to a series of redefinitions of current design practices beyond the ‘problem-solving’ of user-centered design, design thinking or co-design approaches. In contrast to these current trends, some designers are increasingly describing their tasks as forms of ‘problem-making’.